The long ride from Singapore : two surgeons on a motorcycle journey across Asia for cancer - Iau, Philip (Marshall Cavendish Editions, 2017)
A compellingly-narrated, thrillingly-portrayed account account of an epic motorcycle journey taken in 2014 from Singapore to Sweden over 100 days. Philip's aim to increase breast cancer awareness makes it more than the run-of-the-mill adventure holiday, but a ride with a cause. Written as an internal monologue, much in keeping with long motorcycle rides where hours are spent alone in a helmet with one's thoughts, this chronicle runs through 17 countries and the entire sweep of the Silk Road. The motorcycles give the author an immediate access to different peoples and cultures, with a unique ch.